Integration of visual art in learning figurative language among EFL English literature undergraduate students / Clara Ling Boon Ing - Clara , Ling Boon Ing (2025)

(untitled)
This research explores the integration of visual arts as a promising area for scholarly research, offering creative approaches that reshape human experience across diverse contexts. The study investigates the potential of incorporating visual arts to enhance the impacts of learning within the realm of literature education. Previous research has shown that students learning English as a Foreign Language (EFL) often face challenges with figurative language, making literary texts difficult to comprehend. To address this, the study employs a systematic Arts-Based Action Research (ABAR) methodology to explore how drawing can help undergraduate EFL students grasp figurative language concepts. Eleven undergraduate EFL students studying English Literature were selected as participants for the main study. This qualitative action research, conducted over three and a half months, examined innovative strategies for incorporating drawing into literature instruction, going beyond the limitations of traditional text-based learning. Through three research cycles, the researcher refined techniques that integrated drawing with cognitive expression, symbolic art, collaborative learning, and textual connections rooted in cultural contexts. Each cycle involved targeted interventions using visual art elements, design principles, visual thinking strategies, and literature learning concepts. Anchored in Richard Mayer’s Cognitive Theory of Multimedia Learning (CTML), the study revealed that by integrating these strategies, participants engaged more deeply with sensory memory, allowing them to better connect with figurative language by drawing on their cultural backgrounds. This study proposed a way to design interventions to integrate visual art – specifically drawing – not simply as an expressive output, but as a structured, sensory-driven and cognitive learning tool that enhances EFL learners’ understanding of figurative language. The findings also demonstrated improvements in the researcher’s teaching practice, emphasizing the importance of focusing on the learning process rather than the outcome. This study makes a significant methodological contribution to the ABAR framework by providing further evidence of its effectiveness in non-Western settings. Additionally, it extends the application of CTML theory, highlighting the benefits of prolonged sensory memory engagement. The research offers practical insights for educators seeking to integrate visual arts into their teaching practices.